2022
DOI: 10.1111/cpf.12763
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the differences in muscle stiffness measured with shear wave elastography and myotonometer during the menstrual cycle in young women

Abstract: This study assessed the differences in muscle stiffness of the medial gastrocnemius (MG) and tibialis anterior (TA) muscles at rest and contraction during ovulation and follicular phase (menstruation) in women with regular menstrual cycle. Thirty-four young healthy women (mean age 21.3 ± 1.3 years) with regular menstrual cycles participated in this study. Stiffness of the TA and MG muscles at rest and voluntary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…This suggests that the quadriceps and medial site of hamstrings (ST) may be affected during the ovulatory phase, when E2 concentrations are higher [11]. On the other hand, in the lower leg muscle group, no periodic changes in stiffness of the PL, TA, or MG were seen [13]. Previous studies also showed site-specific variations, suggesting that mechanical properties may exhibit site-specific changes.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This suggests that the quadriceps and medial site of hamstrings (ST) may be affected during the ovulatory phase, when E2 concentrations are higher [11]. On the other hand, in the lower leg muscle group, no periodic changes in stiffness of the PL, TA, or MG were seen [13]. Previous studies also showed site-specific variations, suggesting that mechanical properties may exhibit site-specific changes.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, the MyotonPRO digital palpation device (Myoton AS, Tallinn, Estonia), which allows objective, noninvasive measurement of mechanical properties, has been used to evaluate muscle mechanical properties [11][12][13]. A study using the MyotonPRO to examine changes in mechanical properties of the thigh musculature during the early follicular, ovulatory, and luteal phases reported that stiffness of the vastus medialis muscle (VM) and semitendinosus muscle (ST) was higher during the ovulatory phase compared to the luteal phase, while the vastus lateralis muscle (VL) and biceps femoris muscle (BF) did not change with the menstrual cycle [11].…”
Section: Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this study suggested that the stage of the cycle in young women should be a consideration when using SWE as a measure of stiffness. 33 Additionally, the effects of physical activity on the shear modulus have been recently found to increase the stiffness of the infraspinatus after short-term activity. 34 The data from this study highlights the importance of attempting to control participant physical activity between measures.…”
Section: Discussionmentioning
confidence: 99%
“…E2 is beneficial for muscle strength in females (21) and may be related to E2 maintaining muscle mass (22), maintaining the satellite cell pool for regeneration (23), influencing contractility via the binding of myosin heavy chains to actin through phosphorylation of the regulatory light chain (22) and protein synthesis (myofibrillar and collagen) (16). Interestingly, lower muscle stiffness has been shown to be correlated with estrogen concentrations (24)(25)(26)(27), which may protect the muscle from injury (28). Conversely, in tendons, E2 has been shown to affect both the collagen synthesis and the mechanical properties of the tissue, showing that females with higher estrogen may have reduced tendon strength (29).…”
mentioning
confidence: 99%